Brucea javanica oil alleviates intestinal mucosal injury induced by chemotherapeutic agent 5-fluorouracil in mice - Zheng, Xinghan; Mai, Liting; Xu, Ying; Wu, Minghui; Chen, Li; Chen, Baoyi; Su, Ziren; Chen, Jiannan; Chen, Hongying; Lai, Zhengquan; Xie, Youliang (Frontiers in Pharmacology, 2023)
Background:Brucea javanica (L.) Merr, has a long history to be an anti-dysentery medicine for thousand of years, which is commonly called “Ya-Dan-Zi” in Chinese. The common liquid preparation of its seed, B. javanica oil (BJO) exerts anti-inflammatory action in gastrointestinal diseases and is popularly used as an antitumor adjuvant in Asia. However, there is no report that BJO has the potential to treat 5-Fluorouracil (5-FU)-induced chemotherapeutic intestinal mucosal injury (CIM). Aim of the study: To test the hypothesis that BJO has potential intestinal protection on intestinal mucosal injury caused by 5-FU in mice and to explore the mechanisms. Materials and methods: Kunming mice (half male and female), were randomly divided into six groups: normal group, 5-FU group (5-FU, 60 mg/kg), LO group (loperamide, 4.0 mg/kg), BJO group (0.125, 0.25, 0.50 g/kg). CIM was induced by intraperitoneal injection of 5-FU at a dose of 60 mg/kg/day for 5 days (from day 1 to day 5). BJO and LO were given orally 30 min prior to 5-FU administration for 7 days (from day 1 to day 7). The ameliorative effects of BJO were assessed by body weight, diarrhea assessment, and H&E staining of the intestine. Furthermore, the changes in oxidative stress level, inflammatory level, intestinal epithelial cell apoptosis, and proliferation, as well as the amount of intestinal tight junction proteins were evaluated. Finally, the involvements of the Nrf2/HO-1 pathway were tested by western blot. Results: BJO effectively alleviated 5-FU-induced CIM, as represented by the improvement of body weight, diarrhea syndrome, and histopathological changes in the ileum. BJO not only attenuated oxidative stress by upregulating SOD and downregulating MDA in the serum, but also reduced the intestinal level of COX-2 and inflammatory cytokines, and repressed CXCL1/2 and NLRP3 inflammasome activation. Moreover, BJO ameliorated 5-FU-induced epithelial apoptosis as evidenced by the downregulation of Bax and caspase-3 and the upregulation of Bcl-2, but enhanced mucosal epithelial cell proliferation as implied by the increase of crypt-localized proliferating cell nuclear antigen (PCNA) level. Furthermore, BJO contributed to the mucosal barrier by raising the level of tight junction proteins (ZO-1, occludin, and claudin-1). Mechanistically, these anti-intestinal mucositis pharmacological effects of BJO were relevant for the activation of Nrf2/HO-1 in the intestinal tissues. Conclusion: The present study provides new insights into the protective effects of BJO against CIM and suggests that BJO deserves to be applied as a potential therapeutic agent for the prevention of CIM.